Anaesthesia for transcervical thymectomy in myasthenia gravis. - Florence, A. M. (Royal College of Surgeons of England, 1984)
A modified technique of total intravenous anaesthesia was used in the management of 22 patients with myasthenia gravis of varying severity undergoing therapeutic transcervical thymectomy. The relatively short-acting intravenous hypnotics, Althesin and etomidate were compared for induction of anaesthesia and for maintenance as a supplement to 50% nitrous oxide in oxygen. Moderately high doses (20 or 25 micrograms/kg) of the potent, synthetic opiate, fentanyl provided analgesia and a level of respiratory depression sufficient to facilitate control of respiration. The induction of anaesthesia was rapid and smooth, completed in under 5 minutes. Reflex response to surgical stimulation was suppressed for extremely variable periods. Complete recovery of consiousness, or adequate spontaneous respiration and of muscle tone was readily achieved, but was more rapid after Althesin (p less than 0.05). Postoperative problems were few. It is suggested that this technique of anaesthesia can provide optimum operating conditions with rapid, complete recovery and consequently low morbidity; the primary requirements of anaesthesia for therapeutic thymectomy.